Upaya Dedolarisasi BRICS dan Implikasinya Terhadap Ekonomi Global dalam Pandangan Ekonomi Islam - Meisa Putri; Nurida Isnaeni; Aditya Pratama (JOURNAL OF SHARIA ECONOMICS, 2022)
In the global financial system, the dominance of the United States Dollar (USD) has created a structural dependency on a single currency, prompting the BRICS countries (Brazil, Rusia, India, China, and South Africa) to initiate dedollarization efforts. This study aims to analyze the dedollarization strategies undertaken by BRICS and to examine their implications through the lens of Islamic economics. Using a qualitative descriptive method with a literature based approach, this research employs secondary data obtained from academic journal, BRICS reports, credible economic new sources, and official press releases. The data were analyzed using a structured meta-analysis approach to identify patterns, similarities, and the strategic relevance of BRICS dedollarization strategies implemented by BRICS: Local Currency Settlement (LCS), New Development Bank (NDB), Contingent Reserve Arrangement (CRA), Cross-Border Interbank Payment System (CIPS), and the Belt and Road Initiative (BRI). These strategies align with Islamic economic principles such as justice (al-‘adl), public interest (maslahah), coorperation (ta’awun), stability (istiqrar), and efficiency (itqam). From an Islamic economic prespective, dedollarization represents not merely an economic policy alternative but a transformative effort toward a more equitable, ethical, and sustainable global monetary system.